A simplified approach to application layer service signalling - Horwitz, Doron Leon (My University, 2011)
The modern approach to complex services has some shortcomings which overcomplicate the implementation of application servers supporting service logic and also the actual structure of these services. Modern service development environments rely heavily on bearer network call/session signalling for the transport of service messages to remote terminals and manipulating bearer streams in the network. This research report looks at the overheads which occur when the bearer network is used as the main transport for distributed service logic and then goes on to propose application layer focused service development as a replacement for this. Service logic developed in the application layer should be constrained to the application layer so as to avoid leaky abstractions and make service development more intuitive to programmers who do not have deep knowledge of telecommunications technologies since the details of the bearer network do not play a part in the application layer. Application layer signalling is introduced as a concept very important to keeping service logic in the application layer, by allowing service messages to bypass the bearer network. In this way, service sessions are started and maintained in the application layer and lower-layer functionality is only called on when bearer network streams are required by a service. A framework is developed to support application layer focused service development. This framework acts as support for decoupled service logic by allowing easy abstracted use of application layer signalling and bearer network functionality. It also provides a simpli ed means for managing service logic. Reusability is also built in in the form of reusable building blocks which abstract out various functionality including that of the bearer network. Using example services designed to be supported within the framework, the ideas of application layer focused service development are proved to simplify service development and o er robust support to services. Whilst this research report does not attempt to standardise the technologies used to constrain service logic in the application layer, it does put forward important concepts which, when implemented, would enhance service development environments by providing a strong platform on which to develop services.